Vaiṣṇava concepts of god: philosophical perspectives - Silvestre, Ricardo Sousa; Herbert, Alan C.; Göcke, Benedikt Paul (Routledge Hindu studies series, 2024)
"This book analyses the concepts of God in Vaisnavism, which is commonly referred to as one of the great Hindu monotheistic traditions. Addressing the question of what attributes God possesses according to particular textual sources and traditions in Vaisnavism, the book analyses Vaisnava traditions and texts in order to locate them within a global philosophical framework. The book is divided into two sections. The first one, God in Vaisnava Texts, deals with concepts of God found in the canonical Vaisnava texts: the Bhavagad Gita, the Bhagavata Purana, the Pancaratras, and the Mahabharata. The second section, God in Vaisnava Traditions, addresses concepts of God found in several Vaisnava traditions and their respective key theologians. As well as the Alvars, five traditional Vaisnava schools- the Sri Vaisnava tradition, the Madhva tradition, the Nimbarka tradition, the Pustimarga tradition, and the Caitanya Vaisnava tradition- and two contemporary ones Ramakrishna's and Swami Bhaktivedanta's are considered. The book combines normative, critical and descriptive elements. Some chapters are philosophical in nature, others are more descriptive, unpacking a specific Vaiṣṇava concept of God for future philosophical analysis and critique. Written by experts who break new ground in presenting and representing a diversity of Vaiṣṇava texts and tradition, the book presents approaches that reflect the amount of philosophical and historical deliberation on the specific issues and divine attributes considered. This book will be of interest to researchers in the fields of philosophy of religion and Indian philosophy, cross-cultural and comparative philosophy, analytic philosophy of religion, Hindu studies, theology and religious studies"--